2001
DOI: 10.1007/s002530000489
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genetic diversity of initial dioxygenases from PAH-degrading bacteria

Abstract: Alpha subunit genes of initial polyaromatic hydrocarbon (PAH) dioxygenases were used as targets for the PCR detection of PAH-degrading strains of the genera Pseudomonas, Comamonas and Rhodococcus which were obtained from activated sludge or soil samples. Sequence analysis of PCR products from several Pseudomonas strains showed that alpha subunits (nahAc allele) of this genus are highly conserved. PCR primers for the specific detection of alpha subunit genes of initial PAH dioxygenases from Pseudomonas strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…The majority of the target sequences represented NDO ␣ genes from uncultured bacteria cloned from groundwater by reverse transcription PCR (GenBank accession numbers AF099748, AF099749, AF099752, AF099753, AF099755 to AF099759, AF099761 to AF099767, AF099769, AF099770, and AF099772 to AF099774) (40). Target NDO ␣ genes from cultured representatives besides nagAc were pahAc, cloned from C. testosteroni (AF252550) (26), nahAc from Burkholderia sp. strain S1-17 (AF448048) and SOD-5b (AF448053), and nahAc from the PAH-degrading bacteria NJ2, NK2, NK3, and Ralstonia sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the target sequences represented NDO ␣ genes from uncultured bacteria cloned from groundwater by reverse transcription PCR (GenBank accession numbers AF099748, AF099749, AF099752, AF099753, AF099755 to AF099759, AF099761 to AF099767, AF099769, AF099770, and AF099772 to AF099774) (40). Target NDO ␣ genes from cultured representatives besides nagAc were pahAc, cloned from C. testosteroni (AF252550) (26), nahAc from Burkholderia sp. strain S1-17 (AF448048) and SOD-5b (AF448053), and nahAc from the PAH-degrading bacteria NJ2, NK2, NK3, and Ralstonia sp.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that these distinctive nag-type NDO ␣ genes may be related to the use of a gentisate pathway such as that for the well-characterized strain Ralstonia sp. strain U2 (26), although this important aspect remains to be determined. C. testosteroni CZ42 presents genes homologous to nagG and nagH encoding salicylate 5-hydroxylase, the enzyme that converts salicylate to gentisate (44).…”
mentioning
confidence: 99%
“…Therefore there is a growing interest in the bioapplication of microorganisms from the gut of earthworms on the bio-transformation of persistent and toxic pollutants during vermifiltration. Using microorganisms to biodegrade toxic and persistent compounds in the environment is now widely recognized as an emerging effective, economic [1] and environmentally sustainable technology [2]. Polychlorinated hydrocarbons such as DDT are mutagenic and toxic to humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated hydrocarbons such as DDT are mutagenic and toxic to humans and animals. They can be present in soil and sediments where they exist for very long periods of time since their biodegradation is very slow [2,3,4,5]. Only 1% of the DDT .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ␣ and ␤ subunits of nitrobenzene dioxygenase (35) have 81% and 77% identity with the respective NDO-P subunits. This clearly indicates that NDO-R is a phylogenetically distant relative of such enzymes that diverged at a very early stage (41). Structures of various ROs are helping explain how the wide range in sequence identities (from greater than 80% to less than 30%) among these enzymes affects substrate preferences.…”
mentioning
confidence: 99%